Management of Eucalypt Plantations - Chaturvedi, A. N. (Indian Forester, 1983)
Eucalypts have been planted on a large scale in India. They are harvested primarily for the production of paper and rayon grade pulp. Eucalypt plantations are managed under simple coppice system. Decrease in productivity has been noticed in second coppice. It may be desirable to rotate Eucalypt plantations with other species to prevent replant disease.